2018
DOI: 10.1177/0091647118795180
|View full text |Cite
|
Sign up to set email alerts
|

Religious Orientation and Subjective Well-being: The Mediating Role of Meaning in Life

Abstract: The present study concerns the relationship between religious orientation, meaning in life, and subjective well-being, as well as the mediating influence of meaning in life on the relationship between religious orientation and subjective well-being. Gender differences in this relationship are also examined. The subjects of the study were 579 university students (33.5% male; Mage = 21.98, SDage = 4.33). Intrinsic religious orientation was found to be a significant predictor of subjective well-being via meaning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 78 publications
(78 reference statements)
1
21
1
3
Order By: Relevance
“…2005). Several studies provide support for the idea that intrinsic religious motivation relates to an enhanced sense of meaning and purpose (e.g., Dezutter, Soenens, and Hutsebaut 2006; Francis and Crea 2016; Francis, Jewell, and Robbins 2010; You and Lim 2019), and this meaning should correspond to having a more integrated, global way of thinking (e.g., Park 2013). The present study finds evidence consistent with these ideas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2005). Several studies provide support for the idea that intrinsic religious motivation relates to an enhanced sense of meaning and purpose (e.g., Dezutter, Soenens, and Hutsebaut 2006; Francis and Crea 2016; Francis, Jewell, and Robbins 2010; You and Lim 2019), and this meaning should correspond to having a more integrated, global way of thinking (e.g., Park 2013). The present study finds evidence consistent with these ideas.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of evidence supporting that intrinsic religious motivation relates to higher‐level, more global cognitive representations is implicit and comes from studies on how religious orientations relate to purpose and meaning in life. Many studies have identified an association between intrinsic religious motivation and sense of purpose in life (e.g., Dezutter, Soenens, and Hutsebaut 2006; Francis and Crea 2016; Francis, Jewell, and Robbins 2010; You and Lim 2019). The association between intrinsic religious motivation and life purpose may be at least partly explained by cognitive processes.…”
Section: Individual Differences Influence How People Thinkmentioning
confidence: 99%
See 2 more Smart Citations
“…People in this type of religious orientation are those in whom religiosity is the main motivation and belief in God is the basis of their actions and behavior. They worship God not only out of a desire to achieve something, but their goal is holiness and thanksgiving to God (You & Lim, 2019).…”
Section: Mckinnonmentioning
confidence: 99%